Increased impairment of cerebral autoregulation in COVID-19 associated pulmonary failure requiring extracorporeal membrane oxygenation - Thudium, Marcus; Kappler, Jochen; Oremek, Maximilian J. G.; Ehrentraut, Stefan Felix; Kornilov, Evgeniya; Marinova, Milka; Putensen, Christian; Soehle, Martin; Schewe, Jens-Christian (Frontiers in Medicine, 2024)
Introduction: Cerebrovascular complications are feared but also commonly reported in patients with COVID-19 requiring extracorporeal membrane oxygenation (ECMO) support therapy. Besides other reasons, a connection between impaired cerebral autoregulation and SARS-CoV-2 infection as a mechanism for an increase in cerebrovascular complications has been hypothesized.In an observational single-center study, we investigated a cohort of 48 patients requiring veno-venous ECMO support therapy with (n=31) and without SARS-CoV-2 infection (n=17). Cerebral autoregulation was assessed with the cerebral oximetry-derived autoregulation index (ORx) based on a moving correlation between arterial pressure and cerebral oximetry.Results: Patients with ECMO support therapy and SARS-CoV-2 experienced more time with impaired cerebral autoregulation than without SARS-CoV-2 (17 ± 9 % vs. 13 ± 9 % (p = 0.027)). Patients with SARS-CoV-2 suffering from cerebrovascular complications had more time with impaired autoregulation than non SARS-CoV-2 patients with these complications (19 ± 9 % vs. 10 ± 4 %, p=0.032).Our results suggest a connection between SARS-CoV-2 and impaired cerebral autoregulation as well as cerebrovascular complications in SARS-CoV-2 patients.